Answer:
Because
, then the solution is unique.
Explanation:
Given
![Ax = b](https://img.qammunity.org/2022/formulas/mathematics/college/yt1zjq4flanu4hjn3ne1s1glwd3pppacom.png)
![Ax=0](https://img.qammunity.org/2022/formulas/mathematics/college/xholqz0bbf6nt8ahmgsotqyakk15225l2e.png)
See comment for complete question
Let there be two solutions x and y.
Such that:
and
![Ay = b](https://img.qammunity.org/2022/formulas/mathematics/college/jfgyqos2v0mipidlaytd42hyko2e6dh7hs.png)
Since:
![Ax = Ay = b](https://img.qammunity.org/2022/formulas/mathematics/college/2ptoz7q1msm5rilr3am2clek8exzpnuggq.png)
Then:
![Ax - Ay = b - b](https://img.qammunity.org/2022/formulas/mathematics/college/63hzzgaou777c66j8b3eebh1d21qdn8frt.png)
![Ax - Ay = 0](https://img.qammunity.org/2022/formulas/mathematics/college/1nbfebvpqehddudwfp9j4fcba8s8sc8dz8.png)
This implies that:
![Ax - Ay = A(x-y) = 0](https://img.qammunity.org/2022/formulas/mathematics/college/txzigrlfzhs3b0ts17hhxog8qvg7ss9l50.png)
The only trivial solution is:
![Ax - Ay = A(x-y) = 0](https://img.qammunity.org/2022/formulas/mathematics/college/txzigrlfzhs3b0ts17hhxog8qvg7ss9l50.png)
Such that:
![x -y = 0](https://img.qammunity.org/2022/formulas/mathematics/college/ar0ljeuhzw4n1p96exqdqx82as76o3kh1w.png)
Then
![x = y](https://img.qammunity.org/2022/formulas/mathematics/high-school/gnzc99xmq2v9vjkbsjz8v4vadi95nrs68q.png)
Because
, then the solution is unique.